Digital Communication on the TikTok Platform in Increasing the Visibility of MSMEs (Study on TikTok Account @rm.padang.unilintau) - Nico Erdian Syaputra; Eraskaita Ginting; Rina Pebriana (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Micro-scale culinary MSMEs are commonly assumed to have limited digital reach due to a lack of capital and a follower base. This study challenges this assumption by analyzing the visibility anomaly on the TikTok account @rm.padang.unilintau, a culinary MSME in Palembang City that managed to achieve 219,200 organic impressions even though it only has 792 followers. A descriptive qualitative approach was used, with data obtained through virtual observation of three sample videos, in-depth interviews with managers and business owners, and digital metric documentation. The analysis refers to the three characteristics of McQuail and Deuze (2020) New Media Theory, hypertextuality, interactivity, and dispersal. The results showed that the use of viral audio hacked the For You Page algorithm through sound-based hypertextual indexing, resulting in a 645% spike in impressions compared to low-popularity audio videos. Stimulation of appetite appeal through the visualization of side dishes without verbal narratives encourages high-intent engagement as well as physical visit conversion. The dispersal of content to the WhatsApp ecosystem expands the reach beyond geographical boundaries without the cost of paid advertising. Overall, the findings prove that the distribution of content in new media is no longer determined by the hierarchy of the number of followers, but rather by the precision of strategy in responding to algorithmic logic. This research offers a digital communication framework based on new media characteristics as an alternative for MSMEs operating with limited marketing capital.